Glimepiride monotherapy versus combination of glimepiride and linagliptin therapy in patients with HNF1A-diabetes: a protocol for a randomised, double-blinded, placebo-controlled trial - Torben Hansen; Tina Vilsbøll; Filip Krag Knop; Alexander Sidelmann Christensen; Heidi Storgaard; Sofie Hædersdal (BMJ Open)
Introduction Hepatocyte nuclear factor 1α (HNF1A)-diabetes is the most common monogenetic subtype of diabetes. Strict glycaemic control is crucial for a good prognosis for patients with HNF1A-diabetes. Sulfonylurea (SU) is used as a first-line therapy in HNF1A-diabetes. However, SU therapy may be problematic as it confers a high risk of hypoglycaemia. We hypothesise that low dose of SU in combination with a dipeptidyl peptidase 4 inhibitor provides a safer and more efficacious treatment in patients with HNF1A-diabetes compared with SU as monotherapy.Methods and analysis In a randomised, double-blinded, crossover study, patients with HNF1A-diabetes will randomly be assigned to 16 weeks of treatment with glimepiride+linagliptin, 4 weeks of washout and 16 weeks of treatment with glimepiride+placebo (or vice versa). Treatment will be evaluated with continuous glucose monitoring and combined meal and bicycle tests conducted at baseline and at the end of each of the two treatment periods. The primary end point is the absolute difference in the mean amplitude of glycaemic excursions between the two treatments (glimepiride+linagliptin vs glimepiride+placebo) at the end of each treatment period.Ethics and dissemination The study protocol is approved by the Danish Medicines Agency, The Scientific-Ethical Committee of the Capital Region of Denmark (H-17014518) and the Danish Data Protection Agency. The trial will be carried out and monitored in compliance with Good Clinical Practice guidelines and in accordance with the latest version of the Declaration of Helsinki. Positive, negative and inconclusive results will be published at scientific conferences and as one or more scientific manuscripts in peer-reviewed journals with authorship in accordance with the International Committee of Medical Journal Editors’ recommendations.Trial registration number 2017-000204-15.